1999
DOI: 10.1006/lich.1999.0241
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antiviral and Cytotoxic Activity of New Zealand Lichens

Abstract: A total of 69 species of lichens have been collected from various locations around New Zealand. Screening of extracts of these species for antimicrobial, antiviral and cytotoxic activity showed a high proportion with biological activity. Active extracts were generally from species known to contain phenolic compounds. Bioactivity-directed isolation work on Cladia retipora, Pseudocyphellaria glabra and P. homoeophylla led to the identification of usnic acid as the main antimicrobial, cytotoxic and antiviral comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 24 publications
2
90
1
2
Order By: Relevance
“…After that, disks were placed onto agar Petri plates and incubated. The inhibitory activity was indicated by clear zones around the disks, and inhibition zone diameters were measured in millimeters after incubation for 24 h at 37 C (Perry et al, 1999). All tests were performed in triplicate.…”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%
“…After that, disks were placed onto agar Petri plates and incubated. The inhibitory activity was indicated by clear zones around the disks, and inhibition zone diameters were measured in millimeters after incubation for 24 h at 37 C (Perry et al, 1999). All tests were performed in triplicate.…”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%
“…also inhibited the growth of malignant cell lines (Ogmundsdottir et al, 1998). Crude extracts from various lichen species were also screened for their cytotoxic activities and some of them were found to be cytotoxic in different cancer cell lines by two different groups (Perry et al, 1999;Bezivin et al, 2003). Recently, antiproliferative effects of several lichen compounds in human platelets were shown due to their inhibitory activities on 12(S)-HETE which has a role in carcinogenesis and metastasation (Bucar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…subuliformis was evaluated, and the researchers observed that ethyl acetate and chloroform extracts had cytotoxic effects 72 h after the treatment in HeLa cells (Manojlović et al 2010). The extracts of 69 lichens species were evaluated in terms of their biological activities, and lichen extracts demonstrated antimicrobial, antiviral and cytotoxic activities (Perry et al 1999). In a study, the cytotoxic activities of eight lichen extracts were investigated in vitro using two murine and four human cancer cell lines (Bezivin et al 2003).…”
Section: Introductionmentioning
confidence: 99%